Pengaruh Konten Islami Tiktok Bertema Fikih dan Akhlak terhadap Pengetahuan Agama Mahasiswa Prodi PAI UIN Palopo - Putri Sintia; Nur Fakhrunnisaa; M Arief (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
The development of social media as a space for disseminating information has presented opportunities as well as challenges in religious learning for students. TikTok, as a digital platform that is popular among the younger generation, provides a variety of Islamic content with the theme of fiqh and morals that have the potential to affect users' religious understanding. This study aims to analyze the influence of Islamic content on TikTok with the theme of fiqh and morals on the religious knowledge of students of the PAI Study Program UIN Palopo. The research method used a quantitative approach with multiple linear regression analysis of 268 respondents selected through random sampling techniques. The results of the study show that the content of fiqh has a positive and significant effect on students' religious knowledge, so that content that contains explanations of the laws of worship can improve religious understanding. Moral content has also proven to be significant, especially because of the presentation of moral values that are simple and relevant to student life. Simultaneously, the two variables contributed 61.3% to the increase in religious knowledge. These findings confirm that TikTok plays a role as an effective informal learning medium, although the limitations of the duration of the content make the understanding formed not always deep. This research implies the need to strengthen digital literacy and students' critical attitudes in filtering religious content so that the understanding obtained is more comprehensive and accurate.